Letter (copy) : Demonstration on Spain: 26 February - Tewson, Vincent
012b-0038-001 International HVT/AC/212 DD/FD 25th May, 1939. Mr. D. H. Daines, London Labour Party, 258-262, Westminster Bridge Road, S.E.1 Dear Mr. Daines, DEMONSTRATION ON SPAIN: 26 FEBRUARY. Your letter of 17th May was sent down to the Labour Party, because there is nobody on our staff of the name of Miller, whereas there is a temporary employee of that name on the Party staff, and it has only now been returned to us, and the source of the enquiry traced. May I thank you for sending to us copy of the resolution adopted at the Trafalgar Square Spain Demonstration on 26th February, which we are keeping in our records. Yours sincerely, Assistant Secretary. 292/946/12b/38